EVALUASI PERTUMBUHAN IKAN GABUS (Channa striata) DIBERI PAKAN MENGANDUNG TEPUNG DAUN KAYU MANIS (Cinnamomum burmannii) - Tamba, Jappi Tua; Komariyah, Siti; Faisal, Teuku Muhammad (JURNAL PERIKANAN TROPIS, 2020)
Cork fish is one of the commodities from the freshwater fisheries sector which is commonly found in rivers, swamps and swamps that have high economic value and high market demand. The availability of cork fish is still limited to the results of their catch in the wild. And efforts to develop cork fish culture are still small due to slow growth in cork fish and the low response of cork fish to commercially-made feed compared to natural feed. This research is intended to improve the growth of cork fish fed with cinnamon leaf flour (Cinnamomumm burnamani) at different doses.The design used in this study was a completely randomized design (CRD) consisting of 4 treatments with 3 replications. The treatments performed were control (P1), addition of 0.5% cinnamon leaf flour (P2), addition of cinnamon leaf flour 1% (P3), and addition of cinnamon leaf flour 1.5% (P4). The research parameters observed were absolute weight, absolute length, daily growth rate, EP, fat in SR fish body, and cork fish water quality. The results showed that the addition of cinnamon leaf flour at a dose of 1% influenced the growth of absolute weight, absolute length, LPH, and EP. The addition of anis wood leaf flour with a dose of 1.5% can reduce fat content in the body of cork fish.Keywords: Canna striata, Cinnamomum burnamni